NILAI-NILAI ESTETIS BENTUK WAYANG KULIT - Timbul Subagya (Institut Seni Indonesia Surakarta, 2013)
The history of wayang (Javanese leather puppets) had through a long process and was influencedby many religions and beliefs. At the beginning, the function of wayang was as a worship tool to theancestral spirits or Hyang, and developed into attraction show today. Leather wayang was drawnen face and converted became en trios quart. Now it became en profil. The revision and thedevelopment of wayang’s forms stillation is synchronized with the social conditions of the society,from their beliefs in animism, Hinduism, and Islamic. The depictions of puppet forms that existtoday are influenced by Islamic sculpture and technical demands to perform the show on a screen.Depictions of leather wayang in en profile forms were done to avoid realistic human portrayal thatis prohibited in Islam.